Potencial cicatrizante do extrato cetônico de Pentaclethra macroloba no processo de reparo de lesões excisionais na pele de camundongos diabéticos - GOMES, Mauricio Ferreira (Universidade Federal do Pará, 2017)
Diabetes Mellitus (DM), a disease that attracts the interest of many health professionals, is a chronic pathology that has become a public health concern in recent years. The disease is divided into diabetes type 1 and type 2 , which causes a dysfunction in insulin / glucose physiology. This deregulation causes significant alterations in some biological events, among them, the cicatrization process. The emergence of injury in to a normal person triggers a cascade of cellular and biochemical reactions Aiming to repair the injured tissue. In patients with diabetes, the repair is slower. Several mechanisms are described as important factors in the delay of the healing process in diabetics, among them, excessive production of reactive oxygen species (ROS), reduction of nitric oxide (NO), reduction of the response to growth factors (GFs) And proteins the insulin signaling pathway . The search for therapeutic forms that can help the tissue repair process is in great demand, Because the rate of people with diabetes is increasing over the years. Thus, it is aimed to find pharmacological alternatives for this aspect, in the present study the characterization of the pharmacological effect of the topical application of the ketone extract of the seed Pentaclethra macroloba (Pracaxi) on the tissue regeneration process in diabetic animals was performed. To evaluate the healing effect, an excisional cutaneous wound with biopsy punch was created in diabetic animals and were subsequently treated by topical application of the extract to evaluate the healing potential of the seed. The effect of the treatment was evaluated by some aspects, such as: wound contraction, Reepithelialization, quantity of inflammatory cells, tissue organization and formation of collagen in the extracellular matrix. The results showed that the pracaxi extract presented a healing effect in diabetic mice, stimulating the tissue reconstruction after skin lesions. In this way, the pracaxi becomes a possible alternative for the treatment of tissue lesions in diabetics because it stimulates the healing cascade promoting the best formation of the extracellular matrix.